Effectiveness of Edible Coating to Preservation of Passion Fruit - Nguyen Phuoc Minh (Journal of Global Pharma Technology, 2016)
Passion fruit (Passiflora edulis) is considered an exotic species with attractive ﬂavor and aroma. This is a rich source of bioactive compounds, as polyphenols. The interest in P. edulis has been increased because of its antioxidant compounds. Passion fruit is generally considered to have a short storage life, because it is a very delicate, perishable fruit. The main problem of postharvest losses associated with passion fruits is rapid loss of firmness. The objective of the present study was to identify the effect of different carrageenan concentrations (1.0%, 1.5%, 2.0%, 2.5%, 3.0%) and storage temperature (8 oC, 12 oC, 16 oC, 20 oC) to the weight loss, firmness, total soluble sugar and ascorbic acid in passion fruit (Passiflora edulis) fruits during preservation. Moreover, shelf life (0 day, 7 days, 14 days, 21 days and 28 days) of passion fruit (Passiflora edulis) fruit in storage also clarified. Results demonstrated that carrageenan 2.5% and storage temperature 8 oC could maintain passion fruit (Passiflora edulis) fruit quality for 28 days without any deterioration. This is an opportunity to develop value‐added products reducing the postharvest losses, improving nutritional value and generating additional revenue for passion fruit growers.Keywords: Passion fruit, Carrageen an, coating, Firmness, Shelf life, Preservation.